A high resolution γ-ray array for the pandora plasma trap - Goasduff, A.; Santonocito, D.; Menegazzo, R.; Capra, S.; Pullia, A.; Raniero, W.; Rosso, D.; Toniolo, N.; Zago, L.; Naselli, E.; Napoli, D. R. (Frontiers in Physics, 2022)
The measurement of β-decay rates in plasma, simulating stellar-like conditions, is of high interest for the investigation of radionuclides involved in nuclear astrophysics processes. In the new PANDORA plasma trap, to be built at the INFN—Laboratori Nazionali del Sud of Catania (Italy), the β-decay rates will be estimated by detecting the γ-rays emitted by the daughter nuclei trapped in the confined plasma. The present work describes the high efficiency High Purity Germanium (HPGe) detector array that will be placed around the magnetic trap for this purpose, as well as the front-end electronics and acquisition system suitable for the array operation in presence of a high counting rate background originating from Bremsstrahlung radiation.